How to conduct surveys : a step-by-step guide Arlene Fink and Jacqueline Kosecoff.. - Fink, Arlene. (Sage Publications, 1985)
"Concise and clearly written, this practical guide examines the nuts and bolts of interview and questionnaire design. It takes the reader through the process of deciding informational needs and hypotheses, choosing a questionnaire or interview format, designing a data collection method, choosing a sample, analyzing the findings, and reporting results."--LOC publisher description.